2020
DOI: 10.1073/pnas.2003620117
|View full text |Cite
|
Sign up to set email alerts
|

Bringing light to ER contacts and a new phase in organelle communication

Abstract: Functioning cells depend on the outward-facing plasma membrane (PM) effectively contacting the endoplasmic reticulum (ER), which serves as a central hub for contacts with mitochondria and other intracellular organelles. The contact sites are critical to intracellular communication because they mediate intermembrane exchange of lipids, ions, and other small molecules that both maintain competent organelles and modulate their activities. The targeting of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…By demonstrating the compatibility of various biophysical techniques on the newly developed membrane mode along with ability to incorporate additional fluorescent fused proteins of interest into the ER by genetic means post GERs production, the authors revealed the potential application of these systems to investigate enzyme functions and lipid metabolism regulated by ER membrane; a field less explored. Notably, in parallel, another studies revealed the ability of ER membranes to exhibit temperature-dependent phase segregation, similar to that seen in plasma membrane (King et al, 2020) as well as the ability of these phases to selectively sort specific ER proteins (Bag et al, 2020). This has a huge implication on various ER-regulated cellular processes and the use of GERVs to address these concerns remains to be investigated.…”
Section: What the Various Available Tools For Exploring Membrane Structure?mentioning
confidence: 83%
“…By demonstrating the compatibility of various biophysical techniques on the newly developed membrane mode along with ability to incorporate additional fluorescent fused proteins of interest into the ER by genetic means post GERs production, the authors revealed the potential application of these systems to investigate enzyme functions and lipid metabolism regulated by ER membrane; a field less explored. Notably, in parallel, another studies revealed the ability of ER membranes to exhibit temperature-dependent phase segregation, similar to that seen in plasma membrane (King et al, 2020) as well as the ability of these phases to selectively sort specific ER proteins (Bag et al, 2020). This has a huge implication on various ER-regulated cellular processes and the use of GERVs to address these concerns remains to be investigated.…”
Section: What the Various Available Tools For Exploring Membrane Structure?mentioning
confidence: 83%
“…Increased synthesis of peptides and other secretory molecules, their accumulation in ER and vesicles, and Ca 2+ - dependent vesicular release—all require a dramatic expansion of ER and its tightly coupled interactions with mitochondria, Golgi apparatus, and other organelles (Sassano and Agostinis, 2019 ). The expanded and highly heterogeneous lipid space (Harayama and Riezman, 2018 ; Santos and Preta, 2018 ) facilitates complex phase transitions among biomolecules, organelles (Bag et al, 2020 ; King et al, 2020 ), and synaptic vesicles (Rohrbough and Broadie, 2005 ). Lipid synthesis occurs in ER, and the current estimates suggest that more than 38,000 different identified lipids composed cellular membranes (Liebisch et al, 2020 ).…”
Section: Endoplasmic Reticulum In Protoneuronal Secretory Cells Might Promote Synaptogenesis In Evolutionmentioning
confidence: 99%
“…Altogether, these observations suggest a putative role for ordered membrane microdomains in maintaining contacts responsible for inter-organellar lipid transfer. It is tempting to speculate on the lipid composition of the domains in the organelles in contact with the ER and the possibility that organellar contacts are mediated by apposing ordered domains; the unconventional large intracellular vesicle method may provide a tool to investigate such organization in intracellular membranes (Bag et al, 2020).…”
Section: Evidence For Lipid Domains At Inter-organelle Contact Sitesmentioning
confidence: 99%